High-precision liquid cooling plate based on 3D printing metal material and preparation process thereof
Patent Information
- Application Number
- CN202511115386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-08-11
AI Technical Summary
本发明制备的高精度液冷板,降低具有高围框,高凸台液冷板的用料,加工和焊接等制造成本;避免3D打印内流道成型困难,多余物控制困难问题;在需要耐磨或承受高温的区域使用铝基碳化硅等材料,其他部位采用普通材料以降低成本并保持韧性和强度;通过在接口处涂敷导电纳米片/相变涂料,形成连续导热网络,显著提升界面热导率,导电纳米片/相变涂料在相变温度点吸收大量潜热,延缓液冷板局部温升,冷却时释放热量,提升热响应速度,缓冲冷热冲击,减少金属接口因温度波动导致的热疲劳应力,延长液冷板寿命;3D打印焊接局部可缓解因加工和其他焊接方式导致的应力集中,提高部件在环境中的可靠性。
Smart Images

Figure CN120985258B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of 3D printing materials technology, specifically a high-precision liquid cooling plate based on 3D printed metal materials and its preparation process. Background Technology
[0002] Additive manufacturing is closely related to welding technology, and many metal 3D printing processes are essentially high-precision, automated welding processes. Welding additive manufacturing is an important branch of metal additive manufacturing, combining traditional welding techniques with modern digital manufacturing methods, and is widely used in aerospace, energy, defense and other fields. Summary of the Invention
[0003] The purpose of this invention is to provide a high-precision liquid cooling plate based on 3D printed metal materials and its manufacturing process. Conventional welding methods (brazing, diffusion welding, electron beam welding, friction stir welding) are used to form a flow channel sealing structure layer, and 3D printing is used to form a surrounding frame and boss structure. This reduces the manufacturing costs of liquid cooling plates with high frames and high bosses, such as material usage, processing, and welding (thinning can increase the number of welds), while avoiding the problems of difficult internal flow channel forming and difficult control of foreign matter in 3D printing.
[0004] The objective of this invention can be achieved through the following technical solutions: A fabrication process for a high-precision liquid-cooled plate based on 3D-printed metal materials includes the following steps: Step 1: Conductive nanosheets / phase change coatings are obtained by coating MXene nanosheet suspensions onto polymer-coated silica phase change microcapsules. Step 2: Two pieces of aluminum-based silicon carbide of the same size (50×50mm) with a content of 55% were subjected to diffusion welding at a welding temperature of 560℃. After the first batch of welding was completed, a welding blank was obtained. Step 3: At the location where welding is required, engrave lines are processed to mark the welding position. Conductive nanosheets / phase change coatings are sprayed onto the welding position with a coating thickness of 2-3mm. Then, using 55% aluminum-based silicon carbide as raw material, 3D printing is used to process and weld at the marked position to obtain a high-precision liquid cooling plate of 3D printed metal material with a sealing structure layer composite material.
[0005] Furthermore, the specific preparation steps of the MXene nanosheet suspension are as follows: A 15-25% hydrochloric acid solution and lithium fluoride were added to a reaction vessel and stirred at 20-25℃ and 400 rpm for 20-30 min. Then titanium aluminum carbide was added, and stirring was continued for 48-50 h. The mixture was centrifuged at 5000-6000 rpm for 3-5 min, filtered, and the filter cake was washed with deionized water and ethanol until the final washing solution was neutral. The mixture was then ultrasonically exfoliated at an argon flow rate of 20-25 mL / min and centrifuged at 5000-6000 rpm for 1-2 min to obtain MXene nanosheet suspension.
[0006] Furthermore, the ratio of hydrochloric acid solution, lithium fluoride, and titanium aluminum carbide is 1-2L: 800-900g: 500-600g.
[0007] Furthermore, the specific preparation steps of polymer-coated silica phase change microcapsules are as follows: Silica phase change microcapsules, Tris-HCl buffer solution with a pH of 8.5, and dopamine were added to a reaction vessel and stirred for 17-19 h at 35-40 °C and 550-600 r / min. After filtration, the filter cake was washed 2-4 times with deionized water and dried under vacuum at 60-70 °C for 1-2 h to obtain polymer-coated silica phase change microcapsules.
[0008] Furthermore, the ratio of silica phase change microcapsules, Tris-HCl buffer solution, and dopamine is 1-1.2 kg: 2-4 L: 400-500 g.
[0009] Furthermore, the specific preparation steps of the silica phase change microcapsules are as follows: Docosane, hexadecyltrimethylammonium bromide, and formamide were added to a reaction vessel and stirred for 30-40 min at 50-60℃ and 500-600 r / min. Then tetraethyl silicate was added and stirring was continued for 4-5 h. A 2.0 M hydrochloric acid solution was added dropwise at a rate of 3-4 mL / min and stirring was continued for 5-6 h. The mixture was kept at this temperature and allowed to stand for 24-26 h. After separation, washing, and vacuum drying at 60-70℃ for 1-2 h, silica phase change microcapsules were obtained.
[0010] Furthermore, the ratio of n-dodecane, hexadecyltrimethylammonium bromide, formamide, tetraethyl silicate, and hydrochloric acid solution is 1-2 kg: 120-130 g: 4-5 L: 800-900 mL: 80-90 mL.
[0011] Furthermore, the specific preparation steps of the conductive nanosheets / phase change coating are as follows: Polymer-coated silica phase change microcapsules, MXene nanosheet suspensions, and N,N-dimethylformamide were added to a reaction vessel and stirred at 20-25℃ and 400 r / min for 4-5 h. Then, epoxy resin powder was added, and stirring was continued for 2-3 h to obtain conductive nanosheets / phase change coatings.
[0012] Furthermore, the ratio of polymer-coated silica phase change microcapsules, MXene nanosheet suspensions, N,N-dimethylformamide, and epoxy resin powder is 800-900g: 1-2L: 3-4L: 120-140g.
[0013] The beneficial effects of this invention are: The high-precision liquid cooling plate prepared by this invention reduces the manufacturing costs of liquid cooling plates with high frames and high protrusions, including material usage, processing, and welding. It avoids the difficulties in forming internal flow channels and controlling foreign matter in 3D printing. Materials such as aluminum-based silicon carbide are used in areas requiring wear resistance or high temperature resistance, while ordinary materials are used in other parts to reduce costs while maintaining toughness and strength. By coating conductive nanosheets / phase change coatings at the interface, a continuous thermally conductive network is formed, significantly improving the interfacial thermal conductivity. The conductive nanosheets / phase change coatings absorb a large amount of latent heat at the phase change temperature point, delaying the local temperature rise of the liquid cooling plate and releasing heat during cooling, thus improving the thermal response speed, buffering thermal shock, reducing thermal fatigue stress at the metal interface caused by temperature fluctuations, and extending the life of the liquid cooling plate. Local 3D printing welding can alleviate stress concentration caused by processing and other welding methods, improving the reliability of components in the environment. Attached Figure Description
[0014] Figure 1 For aluminum-based silicon carbide diffusion welding of cold plate blanks.
[0015] Figure 2 This is a partial schematic diagram of the 3D printed liquid cooling plate frame.
[0016] Figure 3 This is a schematic diagram of a 3D printed liquid cooling plate boss.
[0017] Figure 4 A schematic diagram of the precision machining of an aluminum-based silicon carbide liquid cooling plate. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1: A fabrication process for a high-precision liquid-cooled plate based on 3D-printed metal materials, comprising the following steps: S1: Add 1-2 kg of n-dodecane, 120-130 g of hexadecyltrimethylammonium bromide and 4-5 L of formamide to a reaction vessel, stir for 30-40 min at 50-60℃ and 500-600 r / min, then add 800-900 mL of tetraethyl silicate, continue stirring for 4-5 h, add 80-90 mL of 2.0 M hydrochloric acid solution dropwise at a rate of 3-4 mL / min, continue stirring for 5-6 h, keep warm and let stand for 24-26 h, separate the contents, wash, and vacuum dry at 60-70℃ for 1-2 h to obtain silica phase change microcapsules.
[0020] S2: Add 1-1.2 kg of silica phase change microcapsules, 2-4 L of Tris-HCl buffer solution with a pH of 8.5 and 400-500 g of dopamine to a reaction vessel, stir for 17-19 h at 35-40 °C and 550-600 r / min, filter, wash the filter cake 2-4 times with deionized water, and vacuum dry at 60-70 °C for 1-2 h to obtain polymer-coated silica phase change microcapsules.
[0021] S3: Add 1-2 L of 15-25% hydrochloric acid solution and 800-900 g of lithium fluoride to the reactor, stir at 20-25℃ and 400 r / min for 20-30 min, then add 500-600 g of titanium aluminum carbide, continue stirring for 48-50 h, centrifuge at 5000-6000 r / min for 3-5 min, filter, wash the filter cake with deionized water and ethanol until the last washing liquid is neutral, ultrasonically peel it at an argon flow rate of 20-25 mL / min, centrifuge at 5000-6000 r / min for 1-2 min to obtain MXene nanosheet suspension.
[0022] S4: Add 800-900g of polymer-coated silica phase change microcapsules, 1-2L of MXene nanosheet suspension and 3-4L of N,N-dimethylformamide to a reactor, stir at 20-25℃ and 400r / min for 4-5h, then add 120-140g of epoxy resin powder and continue stirring for 2-3h to obtain conductive nanosheets / phase change coating.
[0023] S5: Using a welding temperature of 560℃, two pieces of aluminum-based silicon carbide of the same size (50×50mm) with a content of 55% are subjected to the first batch of diffusion welding. After the first batch of welding is completed, a welding blank is obtained. At the position to be welded, lines are processed to mark the welding position. Conductive nanosheets / phase change coatings are sprayed onto the welding position with a thickness of 2-3mm. Then, using aluminum-based silicon carbide with a content of 55% as raw material, 3D printing is used to process and weld at the marked position to obtain a high-precision liquid cooling plate of 3D printed metal material with a sealing structure layer composite material.
[0024] Example 2: A fabrication process for a high-precision liquid-cooled plate based on 3D-printed metal materials, comprising the following steps: S1: Add 1.5 kg of n-dodecane, 125 g of hexadecyltrimethylammonium bromide and 4.5 L of formamide to a reaction vessel, stir at 55 °C and 550 r / min for 35 min, then add 850 mL of tetraethyl silicate, continue stirring for 4.5 h, add 85 mL of 2.0 M hydrochloric acid solution dropwise at a rate of 3.5 mL / min, continue stirring for 5.5 h, keep warm and let stand for 25 h, separate the contents, wash, and vacuum dry at 65 °C for 1.5 h to obtain silica phase change microcapsules.
[0025] S2: 1.1 kg of silica phase change microcapsules, 3 L of Tris-HCl buffer solution with a pH of 8.5 and 450 g of dopamine were added to a reaction vessel and stirred for 18 h at 37.5 °C and 575 r / min. The mixture was filtered, and the filter cake was washed three times with deionized water and dried under vacuum at 65 °C for 1.5 h to obtain polymer-coated silica phase change microcapsules.
[0026] S3: Add 1.5 L of 20% hydrochloric acid solution and 850 g of lithium fluoride to the reactor, stir at 22.5 °C and 400 r / min for 25 min, then add 550 g of titanium aluminum carbide, continue stirring for 49 h, centrifuge at 5500 r / min for 4 min, filter, wash the filter cake with deionized water and ethanol until the last washing liquid is neutral, ultrasonically peel it at an argon flow rate of 22.5 mL / min, centrifuge at 5500 r / min for 1.5 min to obtain MXene nanosheet suspension.
[0027] S4: Add 850g of polymer-coated silica phase change microcapsules, 1.5L of MXene nanosheet suspension and 3.5L of N,N-dimethylformamide to a reactor and stir at 22.5℃ and 400r / min for 4.5h. Then add 130g of epoxy resin powder and continue stirring for 2.5h to obtain conductive nanosheets / phase change coating.
[0028] S5: Using a welding temperature of 560℃, two pieces of aluminum-based silicon carbide of the same size (50×50mm) with a content of 55% were subjected to the first batch of diffusion welding. After the first batch of welding was completed, a welding blank was obtained. The welding positions were marked by machining lines at the locations to be welded. Conductive nanosheets / phase change coatings were sprayed onto the welding positions with a thickness of 2.5mm. Then, using aluminum-based silicon carbide with a content of 55% as raw material, 3D printing was used to process and weld the marked positions to obtain a high-precision liquid cooling plate of 3D printed metal material with a sealing structure layer composite material.
[0029] Example 3: A fabrication process for a high-precision liquid-cooled plate based on 3D-printed metal materials, comprising the following steps: S1: Add 2 kg of n-dodecane, 130 g of hexadecyltrimethylammonium bromide and 5 L of formamide to a reaction vessel, stir for 40 min at 60 °C and 600 r / min, then add 900 mL of tetraethyl silicate, continue stirring for 5 h, add 90 mL of 2.0 M hydrochloric acid solution dropwise at a rate of 4 mL / min, continue stirring for 6 h, keep warm and let stand for 26 h, separate the contents, wash, and vacuum dry at 70 °C for 2 h to obtain silica phase change microcapsules.
[0030] S2: 1.2 kg of silica phase change microcapsules, 4 L of Tris-HCl buffer solution with a pH of 8.5 and 500 g of dopamine were added to a reaction vessel and stirred at 40 °C and 600 r / min for 19 h. After filtration, the filter cake was washed four times with deionized water and dried under vacuum at 70 °C for 2 h to obtain polymer-coated silica phase change microcapsules.
[0031] S3: Add 2L of 25% hydrochloric acid solution and 900g of lithium fluoride to the reactor, stir at 25℃ and 400r / min for 30min, then add 600g of titanium aluminum carbide, continue stirring for 50h, centrifuge at 6000r / min for 5min, filter, wash the filter cake with deionized water and ethanol until the last washing liquid is neutral, ultrasonically peel it at an argon flow rate of 25mL / min, centrifuge at 6000r / min for 2min to obtain MXene nanosheet suspension.
[0032] S4: Add 900g of polymer-coated silica phase change microcapsules, 2L of MXene nanosheet suspension and 4L of N,N-dimethylformamide to a reactor, stir at 25℃ and 400r / min for 5h, then add 140g of epoxy resin powder and continue stirring for 3h to obtain conductive nanosheets / phase change coating.
[0033] S5: Using a welding temperature of 560℃, two pieces of aluminum-based silicon carbide of the same size (50×50mm) with a content of 55% were subjected to the first batch of diffusion welding. After the first batch of welding was completed, a welding blank was obtained. The welding positions were marked by machining lines at the positions to be welded. Conductive nanosheets / phase change coatings were sprayed onto the welding positions with a thickness of 3mm. Then, using aluminum-based silicon carbide with a content of 55% as raw material, 3D printing was used to process and weld the marked positions to obtain a high-precision liquid cooling plate of 3D printed metal material with a sealing structure layer composite material.
[0034] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A fabrication process for a high-precision liquid-cooled plate based on 3D-printed metal materials, characterized in that, Includes the following steps: Step 1: Conductive nanosheets / phase change coatings are obtained by coating MXene nanosheet suspensions onto polymer-coated silica phase change microcapsules. Step 2: Using a welding temperature of 560℃, two pieces of aluminum-based silicon carbide of the same size (50×50mm) with a content of 55% were subjected to the first heat of diffusion welding. After the first heat of welding was completed, a welding blank was obtained. Step 3: At the location where welding is required, engrave lines are processed to mark the welding position. Conductive nanosheets / phase change coatings are sprayed onto the welding position with a coating thickness of 2-3mm. Then, using aluminum-based silicon carbide with a content of 55% as raw material, 3D printing is used to process and weld at the marked position to obtain a high-precision liquid cooling plate of 3D printed metal material with a sealing structure layer composite material. The specific preparation steps of the MXene nanosheet suspension are as follows: A 15-25% hydrochloric acid solution and lithium fluoride were added to a reaction vessel and stirred at 20-25℃ and 400 rpm for 20-30 min. Then titanium aluminum carbide was added, and stirring was continued for 48-50 h. The mixture was centrifuged at 5000-6000 rpm for 3-5 min, filtered, and the filter cake was washed with deionized water and ethanol until the final washing solution was neutral. The mixture was then ultrasonically exfoliated at an argon flow rate of 20-25 mL / min and centrifuged at 5000-6000 rpm for 1-2 min to obtain MXene nanosheet suspension. The specific preparation steps of the polymer-coated silica phase change microcapsules are as follows: Silica phase change microcapsules, Tris-HCl buffer solution with a pH of 8.5, and dopamine were added to a reaction vessel and stirred for 17-19 h at 35-40 °C and 550-600 r / min. After filtration, the filter cake was washed 2-4 times with deionized water and dried under vacuum at 60-70 °C for 1-2 h to obtain polymer-coated silica phase change microcapsules.
2. The fabrication process of a high-precision liquid-cooled plate based on 3D printed metal materials according to claim 1, characterized in that, The ratio of hydrochloric acid solution, lithium fluoride, and titanium aluminum carbide is 1-2L: 800-900g: 500-600g.
3. The fabrication process of a high-precision liquid-cooled plate based on 3D-printed metal materials according to claim 1, characterized in that, The ratio of silica phase change microcapsules, Tris-HCl buffer solution, and dopamine is 1-1.2 kg: 2-4 L: 400-500 g.
4. The fabrication process of a high-precision liquid-cooled plate based on 3D-printed metal materials according to claim 1, characterized in that, The specific preparation steps of the silica phase change microcapsules are as follows: Docosane, hexadecyltrimethylammonium bromide, and formamide were added to a reaction vessel and stirred for 30-40 min at 50-60℃ and 500-600 r / min. Then tetraethyl silicate was added and stirring was continued for 4-5 h. A 2.0 M hydrochloric acid solution was added dropwise at a rate of 3-4 mL / min and stirring was continued for 5-6 h. The mixture was kept at this temperature and allowed to stand for 24-26 h. After separation, washing, and vacuum drying at 60-70℃ for 1-2 h, silica phase change microcapsules were obtained.
5. The fabrication process of a high-precision liquid-cooled plate based on 3D-printed metal materials according to claim 4, characterized in that, The ratio of n-dodecane, hexadecyltrimethylammonium bromide, formamide, tetraethyl silicate, and hydrochloric acid solution is 1-2 kg: 120-130 g: 4-5 L: 800-900 mL: 80-90 mL.
6. The fabrication process of a high-precision liquid-cooled plate based on 3D-printed metal materials according to claim 1, characterized in that, The specific preparation steps of the conductive nanosheets / phase change coating are as follows: Polymer-coated silica phase change microcapsules, MXene nanosheet suspensions, and N,N-dimethylformamide were added to a reaction vessel and stirred at 20-25℃ and 400 r / min for 4-5 h. Then, epoxy resin powder was added, and stirring was continued for 2-3 h to obtain conductive nanosheets / phase change coatings.
7. The fabrication process of a high-precision liquid-cooled plate based on 3D-printed metal materials according to claim 6, characterized in that, The ratio of the polymer-coated silica phase change microcapsules, MXene nanosheet suspensions, N,N-dimethylformamide and epoxy resin powder is 800-900g: 1-2L: 3-4L: 120-140g.
8. A high-precision liquid-cooled plate based on 3D-printed metal materials, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Combined process method for connecting and destressing multifunctional composite component
CN114799586A
Production method of battery module liquid cooling plate
CN116329686A